2017
DOI: 10.1097/md.0000000000006783
|View full text |Cite
|
Sign up to set email alerts
|

The impact and financial burden of pulmonary arterial hypertension on patients and caregivers

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 17 publications
2
76
0
Order By: Relevance
“…The present study indicated that the significant influencing factors of anxiety/depression were the financial situation and right ventricular enlargement. The conclusion that the financial situation as a significant influencing factor of anxiety/depression was in accordance with a previous descriptive study by our group, according to which patients with PH reported that the financial burden due to their diseases was heavy and they had emotional problems (24). It appears that the self-assessment of the mental condition and QoL by patients, together with clinical parameters determined by clinicians, may be part of a comprehensive assessment.…”
Section: % CI --------------------------------------------------supporting
confidence: 90%
“…The present study indicated that the significant influencing factors of anxiety/depression were the financial situation and right ventricular enlargement. The conclusion that the financial situation as a significant influencing factor of anxiety/depression was in accordance with a previous descriptive study by our group, according to which patients with PH reported that the financial burden due to their diseases was heavy and they had emotional problems (24). It appears that the self-assessment of the mental condition and QoL by patients, together with clinical parameters determined by clinicians, may be part of a comprehensive assessment.…”
Section: % CI --------------------------------------------------supporting
confidence: 90%
“…In the United States, the cost for bosentan and epoprostenol can be as much as $25,000 and $35,000 per month, respectively (Wryobeck, Lippo, McLaughlin, Riba, & Rubenfire, 2007). According to a national survey in China, over 50% of PAH patients do not use any kind of PAH‐specific therapies due to the financial burden (Zhai et al, 2017). It is thus important to develop and identify new medications that have equal or higher efficacy but are affordable, readily available, and easily administered for patients with PAH.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with PAH have significant psychological morbidity. In fact, the diagnosis of PAH creates emotional and psychological distress, reflected as feelings of frustration, anger, low self-esteem and worthlessness [25,27]. Indeed, patients with worse functional class and reduced exercise capacity often have a higher prevalence of depression [10].…”
Section: Health-related Quality Of Life In Pahmentioning
confidence: 99%
“…Worsening HRQoL in patients with PAH is associated with reduced social activity and emotional wellbeing [11]. Patients frequently face a loss of financial security and social status, as they become unable to maintain employment [10], travel obligations or social activities [25,27]. In addition, marital relationships can suffer as sexual intimacy diminishes given physical limitations, reduced self-esteem and a partner's fear of affecting the patient's condition [25].…”
Section: Health-related Quality Of Life In Pahmentioning
confidence: 99%